Contrast reversal of the iris and sclera increases the face sensitive N170 - Jantzen, Kelly J.; McNamara, Nicole; Harris, Adam; Schubert, Anna; Brooks, Michael; Seifert, Matthew; Symons, Lawrence A. (Frontiers in Human Neuroscience, 2022)
Previous research has demonstrated that reversing the contrast of the eye region, which includes the eyebrows, affects the N170 ERP. To selectively assess the impact of just the eyes, the present study evaluated the N170 in response to reversing contrast polarity of just the iris and sclera in upright and inverted face stimuli. Contrast reversal of the eyes increased the amplitude of the N170 for upright faces, but not for inverted faces, suggesting that the contrast of eyes is an important contributor to the N170 ERP.